MAXIMIZING CUSTOMER VALUE AND CORPORATE IMAGE THROUGH STRATEGIC MARKETING AND DISTRIBUTION IN PUBLIC WATER SERVICES - Pertiwi, Dewi (Jurnal Riset Bisnis dan Manajemen, 2025)
Regional Drinking Water Company (PDAM) aims to support regional and national development by providing clean, healthy drinking water, unlike profit-oriented private companies. This study examines the impact of PDAM’s marketing and distribution strategies on customer value and its implications for corporate image in the Bandung Metropolitan Area. The research uses descriptive and verificative methods, with data collected through interviews, questionnaires, observations, and literature reviews. Cluster random sampling was applied to select respondents, and data analysis employed Structural Equation Modeling (SEM). Results reveal that the marketing and distribution strategies, customer value, and corporate image of PDAM are generally suboptimal. Both marketing and distribution strategies significantly influence customer value, both simultaneously and partially. Additionally, customer value has a positive effect on corporate image. These findings highlight the critical role of improving marketing and distribution efforts to enhance customer satisfaction and strengthen PDAM's corporate image in the Bandung Metropolitan Area